Eco-Friendly Antifouling Coating Technologies for Marine Vessels: Material Science Advances and Environmental Compliance Under IMO Regulations - Tri Cahyadi; Marihot Simanjuntak; Natanael Suranta; Larsen Barasa; Marudut Bernadtua Simanjuntak (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Marine biofouling — the progressive accumulation of microorganisms, algae, barnacles, and other aquatic organisms on submerged vessel hull surfaces — imposes a 25–40% fuel consumption penalty at the macrofouling stage and simultaneously facilitates the transport of non-indigenous invasive species across biogeographic barriers, constituting both a significant GHG emission driver and a global ecological threat. This study examines antifouling coating technology adoption and compliance in the Indonesian domestic fleet, evaluates alternative antifouling technologies against environmental performance, fuel saving benefit, and IMO regulatory compliance dimensions under Indonesian tropical operating conditions, and develops prioritized technology adoption and regulatory implementation recommendations. A mixed-methods design was employed, combining hull inspection and documentary review of 84 domestic vessels across four vessel type categories at three Indonesian port areas, stakeholder interviews with 46 participants across operator, shipyard, regulatory, industry, and NGO groups, and comparative technology performance assessment of four antifouling system categories. Results reveal that while 86% of vessels achieve AFS Convention (TBT prohibition) compliance, only 6.5% fully comply with IMO Biofouling Management Guidelines. A full fleet eco-upgrade across the 84-vessel sample would deliver annual fuel savings of 12,980 tonnes HFO and 40,500 tonnes CO₂ at a positive 15-year fleet NPV of USD 16.6 million. Cost barriers — with eco-friendly coatings carrying a 2–4× unit price premium — are identified as the primary adoption constraint. Three priority policy recommendations are proposed: mandatory Biofouling Management Plan documentation for all vessels exceeding 400 GT; a green maritime financing facility for eco-coating upgrades during drydocking; and mandatory hull fouling performance reporting within the CII monitoring framework.